Gender Participation in Vegetable Cultivation in Kashmir Valley - S. H. Baba, S. A. Ganaie, Musavir Yousuf, Shoaib Yousuf, (Indian Journal of Extension Education, 2022)
An attempt was made in this paper to examine the growth of vegetable sector in Kashmir valley and impact of Technology Mission, and the pattern of gender participation in different activities and decisions involved in vegetable cultivation. The results revealed that R&D efforts under Mini Mission-II encompassing various vegetable development programmes have significantly improved area and production of vegetables in the valley. It was observed that although women dominated in some operations of vegetable cultivation but in totality male participation was found more important. As far as various decisions relating to vegetable cultivation are concerned, the role of women in majority of the cases was supportive in nature while the dominative role in most of the cases was performed by men. On the basis of the findings, it is suggested that education and extension facilities to female should be provided to broaden their out ward horizon that can ultimately enhance their participation in decision-making.